“A medio borrar” en el origen: de Saer a Saer - Valentina Litvan (Cuadernos LIRICO)
When Juan José Saer leaves Argentina to arrive in France, he has already published several books. Nonetheless, that journey in 1968 marks a crucial moment that will leave its traces in the process of writing. In his manuscripts, we perceive a first French period; particularly prolific in which the author tries out a voice that comes from a different position. I propose to talk about a poetics of displacement, or even a poetic of the otherness that, beyond finding an echo in the theme of the journey and the fracturing of the self, founds itself on new gestures of creation. An evident example of this is the story “A medio borrar,” dated in 1971 although its first manuscript already appeared in an Argentinean notebook in 1967. In-between the two versions of the story, the journey finds a place in the writing through several mechanisms that I briefly analyze in this work.